2016
DOI: 10.1370/afm.1961
|View full text |Cite
|
Sign up to set email alerts
|

Should Clinicians Recommend E-cigarettes to Their Patients Who Smoke? No.

Abstract: To read or post commentaries in response to this article, see it online at http://www.annfammed.org/content/14/4/302.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…These findings are consistent with concerns echoed by many studies that have shown clinicians misgivings about the effectiveness of the devices. 20,21,26,[31][32][33][34] Interestingly, more than a third of the respondents were unsure about the effectiveness of e-cigarettes, indicating that family physicians are concerned about the uncertainty regarding the efficacy of e-cigarettes as substitutes for cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with concerns echoed by many studies that have shown clinicians misgivings about the effectiveness of the devices. 20,21,26,[31][32][33][34] Interestingly, more than a third of the respondents were unsure about the effectiveness of e-cigarettes, indicating that family physicians are concerned about the uncertainty regarding the efficacy of e-cigarettes as substitutes for cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…First, the items were created based on the literature on e-cigarettes. 11,20,21,26 The questions generated were reviewed by 2 family physicians and a behavioral scientist, based on their experiences working with tobacco users, to ensure that the questions had face validity. We later sought input from faculty and staff of the KUSM-W DFCM, who ensured that the questions were intuitively understandable.…”
Section: Participants and Study Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 48% (Kandra et al, 2014) and 65% (Steinberg et al, 2015) of US physicians report being asked by patients about ecigarettes and such evidence has resulted in guidelines for practitioners responding to such requests (Mendelsohn and Gartner, 2015). Nonetheless, VNPs remain contentious (McNeill, 2016;Meernik and Goldstein, 2016) with opponents highlighting uncertainty around long-term safety, and expressing fear they will renormalise smoking, thus potentially encouraging uptake among young people (Morphett et al, 2016;van der Eijk, 2016).…”
Section: Tobacco Harm Reduction and Vaporised Nicotine Productsmentioning
confidence: 99%